Clinical application of live biotherapeutic products in infectious diseases - Navalkele, Bhagyashri D.; Chopra, Teena (Frontiers in Microbiomes, 2024)
Live biotherapeutics products (LBP) are a novel range of therapeutic options in medicine. In this review, authors discuss basic composition and mechanism of action of LBP, provide a comprehensive focused overview of published in vitro and in vivo studies on efficacy of LBP for prevention and treatment of infectious diseases such as viral (HIV, COVID-19), bacterial (C.difficile infection, bacterial vaginosis, multi-drug resistant organisms) and fungal (Candida) organisms. This review should be of interest to clinicians to understand the broad application of LBP in infectious diseases world beyond recurrent C.difficile infection and to researchers on unexplored prospects of LBP and the need for further investigation in this emerging field to improve its clinical application.